Zimbabwe's national AIDS levy: A case study. Issue 1 (1st January 2016) - Bhat, Nisha; Kilmarx, Peter H.; Dube, Freeman; Manenji, Albert; Dube, Medelina; Magure, Tapuwa
Abstract: Background : We conducted a case study of the Zimbabwe National AIDS Trust Fund ('AIDS Levy') as an approach to domestic government financing of the response to HIV and AIDS. Methods : Data came from three sources: a literature review, including a search for grey literature, review of government documents from the Zimbabwe National AIDS Council (NAC), and key informant interviews with representatives of the Zimbabwean government, civil society and international organizations. Findings : The literature search yielded 139 sources, and 20 key informants were interviewed. Established by legislation in 1999, the AIDS Levy entails a 3% income tax for individuals and 3% tax on profits of employers and trusts (which excluded the mining industry until 2015). It is managed by the parastatal NAC through a decentralized structure of AIDS Action Committees. Revenues increased from inception to 2006 through 2008, a period of economic instability and hyperinflation. Following dollarization in 2009, annual revenues continued to increase, reaching US$38.6 million in 2014. By policy, at least 50% of funds are used for purchase of antiretroviral medications. Other spending includes administration and capital costs, HIV prevention, and monitoring and evaluation. Several financial controls and auditing systems are in place. Key informants perceived the AIDS Levy as a 'homegrown' solution that provided country ownership and reduced dependence on donor funding, but called for further increased transparency, accountability, and reduced administrative costs, as well as recommended changes to increase revenue. Conclusions : The Zimbabwe AIDS Levy has generated substantial resources, recently over US$35 million per year, and signals an important commitment by Zimbabweans, which may have helped attract other donor resources. Many key informants considered the Zimbabwe AIDS Levy to be a best practice for other countries to follow.